Flood frequency and flood intensity changes in the post embankment period in the Kosi sub-basin India: Impact of location, caste, and class on the flood vulnerability of the marginal communities - Sahani, Ranjeet Kumar; Badiger, Shrinivas; Samrat, Abhishek; Krishnan, Siddhartha (Frontiers in Water, 2023)
The overall precipitation in the state of Bihar, India is showing a decreasing trend both annually and seasonally, and yet extreme flood events are on the rise. The Kosi river embankments built to safeguard the communities against flood risk have divided the communities into those living inside and outside of the embankment. Our paper employs a unique interdisciplinary approach to analysing both the biophysical and socio-institutional causalities of increasing flood events. We have found that the daily, as well as monthly rainfall alone, are not responsible for extreme flood events. The extreme rainfall events in the summer monsoon also do not increase the odds of flooding. Therefore, we conclude that precipitation itself is not the main factor affecting communities but a combination of other socio-institutional factors including embedded vulnerabilities of certain communities. Our statistical analysis correlating daily and monthly gridded rainfall to the odds of flooding at the district level suggest that there are fewer flood events in the presence of the embankments across all years. However, the primary data from household interviews and field observations confirm that the frequency and intensity of floods have increased in the post-embankment period. We found that the breaching of the river embankments is one of the major factors responsible for major floods outside of the embankments. The geomorphology of the river Kosi also makes it highly susceptible to recurring floods because it forms one of the largest inland deltas in North Bihar. Flood protection structures such as embankments exacerbate the magnitude of the floods by jacketing the heavy sediment load and thus raising the riverbeds and exacerbating the intensity and the flood duration not just for the communities living inside but also for those living outside of these embankments. These communities perceive that they have become more vulnerable to flood risk with a declining standard of living in the Kosi villages caused by a lack of proper roads, economic opportunities, educational institutions, public utilities and healthcare facilities, especially in areas with river embankments.